33=(m-5)*m

Simple and best practice solution for 33=(m-5)*m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33=(m-5)*m equation:


Simplifying
33 = (m + -5) * m

Reorder the terms:
33 = (-5 + m) * m

Reorder the terms for easier multiplication:
33 = m(-5 + m)
33 = (-5 * m + m * m)
33 = (-5m + m2)

Solving
33 = -5m + m2

Solving for variable 'm'.

Reorder the terms:
33 + 5m + -1m2 = -5m + 5m + m2 + -1m2

Combine like terms: -5m + 5m = 0
33 + 5m + -1m2 = 0 + m2 + -1m2
33 + 5m + -1m2 = m2 + -1m2

Combine like terms: m2 + -1m2 = 0
33 + 5m + -1m2 = 0

Begin completing the square.  Divide all terms by
-1 the coefficient of the squared term: 

Divide each side by '-1'.
-33 + -5m + m2 = 0

Move the constant term to the right:

Add '33' to each side of the equation.
-33 + -5m + 33 + m2 = 0 + 33

Reorder the terms:
-33 + 33 + -5m + m2 = 0 + 33

Combine like terms: -33 + 33 = 0
0 + -5m + m2 = 0 + 33
-5m + m2 = 0 + 33

Combine like terms: 0 + 33 = 33
-5m + m2 = 33

The m term is -5m.  Take half its coefficient (-2.5).
Square it (6.25) and add it to both sides.

Add '6.25' to each side of the equation.
-5m + 6.25 + m2 = 33 + 6.25

Reorder the terms:
6.25 + -5m + m2 = 33 + 6.25

Combine like terms: 33 + 6.25 = 39.25
6.25 + -5m + m2 = 39.25

Factor a perfect square on the left side:
(m + -2.5)(m + -2.5) = 39.25

Calculate the square root of the right side: 6.264982043

Break this problem into two subproblems by setting 
(m + -2.5) equal to 6.264982043 and -6.264982043.

Subproblem 1

m + -2.5 = 6.264982043 Simplifying m + -2.5 = 6.264982043 Reorder the terms: -2.5 + m = 6.264982043 Solving -2.5 + m = 6.264982043 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + m = 6.264982043 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + m = 6.264982043 + 2.5 m = 6.264982043 + 2.5 Combine like terms: 6.264982043 + 2.5 = 8.764982043 m = 8.764982043 Simplifying m = 8.764982043

Subproblem 2

m + -2.5 = -6.264982043 Simplifying m + -2.5 = -6.264982043 Reorder the terms: -2.5 + m = -6.264982043 Solving -2.5 + m = -6.264982043 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + m = -6.264982043 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + m = -6.264982043 + 2.5 m = -6.264982043 + 2.5 Combine like terms: -6.264982043 + 2.5 = -3.764982043 m = -3.764982043 Simplifying m = -3.764982043

Solution

The solution to the problem is based on the solutions from the subproblems. m = {8.764982043, -3.764982043}

See similar equations:

| v/5=3 | | 441+659=v | | 677+n=896 | | n-7=48 | | 719+n=803 | | n-8=32 | | n/4 | | 9*(-7)+3+7=x | | -8+3*5+2=x | | 1-4-5*2=x | | 7*8-9+4=x | | -9(x-7)=3(x-5) | | 6=-16t^2+30t+15 | | -3-1*3-8=x | | -6-7*6*5=x | | 1(x-3)=2.5 | | 3-3*(-5)=x | | -7+1*2=x | | 3-2(x-3)=2.5 | | 3+7*(-9)=x | | w=u+xy | | 9n+13m-8n+m= | | a/5+7=12 | | 2y+1=1 | | 4+x/7=8 | | 2x+y=9*3 | | 6x+36=14x-46 | | 4x+3=83 | | 2(x-2)=9 | | -3(f-2)=21 | | -2(x+1)=12 | | 3(f-2)=21 |

Equations solver categories